(untitled) (Cuadernos de Análisis y Debate sobre Músicas Latinoamericanas Contemporáneas, 2020)
This article studies the outstanding aspects of the aesthetic proposal of the Argentine composer Matías Giuliani, specifically investigating his production of scenic music, which is characterized by the collaborative work with the performers, where operative processes are articulated that involve a review of the concert as an institution and an opening towards new conceptions around the intervening agents and their functions, based on experimentation in the instances of compositional process, notation, rehearsal, recording, staging and interpretation.